Critical issues and opportunities of emergency psychiatry in Italian emergency departments - Carlo Fraticelli; Ilaria Casolaro; Massimiliano Nigro (Emergency Care Journal, 2019)
In Italy emergency physicians are the front line of care for patients with medical conditions such as trauma, heart attacks, strokes or psychiatric disorders. Triage represents the first clinical contact with the person to determine urgency of care, and includes initial risk assessment and determination of observation level. It is necessary to undertake mental health triage for all service users on entry to the Emergency Department (ED), alongside physical health triage. The recourse to emergency services for psychiatric complaints is increasing and ED providers are often the first contact a patient will have with psychiatric care. The organization of Italian EDs is constantly evolving under the pressure of various external forces (population aging, increasing use of new substances, immigration, choices of economic policy, and technological development). The psychiatric emergency service contact represents a key to addressing the presenting problem and it is a critical link for continuity of care. The management of psychiatric disorders is an evolving issue in Italy as in other countries. Research increasingly suggests the importance of specific training for EDs teams in order to provide appropriate handling in acute settings. Psychiatrists and ED physicians can – and should – play a fundamental role in promoting a targeted and shared training for emergency services to deal with crisis according to evidence-based medicine. Service organization, legal issues, safety, training and education are not well defined and established and still imply improvisation, while they deserve attention as fundamental prerequisite to implement specific treatment guidelines.